KATA KERJA DALAM BAHASA INGGRIS DAN BAHASA SANGIR SUATU ANALISIS KONTRASTIF - SIKOME, ALINTIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The research which entitled ‘Verbs in English and Sangir Language: A Contrastive Analysis’ aims at identifying and analyzing the kinds of verbs in these two languages and finding out the differences between both languages. The English data have been collected from English books and articles in Tempo Co. Jakarta, whereas the data of Sangihe Language have been collected from informants and song of Sangir language. In English the kinds of verbs may be classified by complement verb and form of verb which involves predicating or linking verbs, transitive or intransitive verbs, reflexive verbs, auxiliary or lexical verbs and finite or non-finite verbs and in Sangir language it concern predicating or linking verbs, transitive or intransitive verbs, lexical verbs and finite verbs. Theoretically, this research gives contribution toward the knowledge development in contrastive analysis especially verbs in English and Sangir language. Practically, this research can be used as a reference for further research. Key words: Kinds of Verbs in English, Sangir Language and Contrastive Analysis